Comparative physiological and immunological impacts of Moringa oleifera leaf and seed water supplements on African catfish (Clarias gariepinus): effects on disease resistance and health parameters - Howyda G. Gaber; Nehal A. Younis; Sohair Y. Saleh (BMC Veterinary Research)
Abstract This study evaluated the differential effects of Moringa oleifera leaf and seed powders (0.8 g/L) as water supplements on the physiological and immunological responses of African catfish (Clarias gariepinus) over six weeks. Leaf supplementation enhanced growth performance (final weight: 120.5 ± 0.7 g & gain% 65.2) and disease resistance, while seed supplementation elicited adverse physiological outcomes. Fish treated with seed powder exhibited reduced growth performance (gain % 11.2), elevated stress markers (glucose: 113.3 ± 3.8 mg/dL; cortisol: 27.4 ± 1.3 μg/dL), and compromised liver function (ALT: 30.2 ± 1.1 U/L; AST: 53.0 ± 1.6 U/L), evident through histological changes. Both treatments modulated immune responses, significantly upregulating pro-inflammatory serum cytokines (TNF-α, IL- 1β, IL- 6) and increasing gene expression in kidney and spleen tissues, with seeds group showing more pronounced elevations (TNF-α: 4.15-fold, IL- 1β: 3.15-fold in spleen) compared to moderate increases in leaves group (TNF-α: 2.48-fold, IL- 1β: 1.62-fold). Oxidant/antioxidant analysis revealed contrasting effects: leaf treatment enhanced superoxide dismutase activity (SOD) and reduced lipid peroxidation, malondialdehyde (MDA), while seed treatment compromised SOD defense and increased oxidative biomarker (MDA). Upon challenge with Aeromonas hydrophila, leaf-treated fish maintained 100% survival, while seed-treated and control groups showed 85% and 60% survival rates, respectively. These findings underscore the potential of M. oleifera leaf powder as an effective water supplement for enhancing growth and disease resistance in aquaculture, while cautioning against the use of seed powder due to its adverse physiological effects.